2019
DOI: 10.2139/ssrn.3396046
|View full text |Cite
|
Sign up to set email alerts
|

Informal Sector and Mobile Financial Services in Developing Countries: Does Financial Innovation Matter?

Abstract: This paper investigates the impact of mobile financial services -MFS (mobile money, and mobile credit and savings) on the informal sector. Using both parametric and non-parametric methods on panel data from 101 emerging and developing countries over the period 2000-15, we find that MFS negatively affect the size of the informal sector. According to estimates derived from propensity score matching, MFS adoption decreases the informal sector size in a range of 2.4 -4.3 percentage points of GDP. These formalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Rotondi and Billari (2017) showed that household users of MM were less likely to have school age children who are not enrolled in school, and this effect was most evident in SSA. Moreover, MM is associated with a declining presence of the shadow economy, suggesting the contribution of MM to economy formalization (Jacolin et al, 2019)…”
Section: Resultsmentioning
confidence: 99%
“…Rotondi and Billari (2017) showed that household users of MM were less likely to have school age children who are not enrolled in school, and this effect was most evident in SSA. Moreover, MM is associated with a declining presence of the shadow economy, suggesting the contribution of MM to economy formalization (Jacolin et al, 2019)…”
Section: Resultsmentioning
confidence: 99%
“…Some informal firms already utilise digital applications and free social media tools to promote their products and services. Empirical evidence shows that adopting mobile financial services reduces the size of the informal sector in developing countries by 2.4 to 4.3 percentage points of gross domestic product (GDP) (Jacolin et al, 2019).…”
Section: African Governments Can Help Increase the Availability And Amentioning
confidence: 99%
“…Several studies have been carried out on the effects of governance on financial inclusion. However, while the effects of institutional factors on traditional financial services, i.e., banking or markets, have been widely discussed in the literature (Beck et al, 2003), their effects on financial inclusion involving mobile money are much less addressed (Jacolin et al, 2019). Similarly, because of the high rate of bankization in developed countries, the need for financial inclusion in emerging or developing countries is evident.…”
Section: An Empirical Look At the Relationship Between Governance Andmentioning
confidence: 99%